Pengaruh Pertumbuhan Perusahaan Pada Nilai Perusahaan Dengan Pengungkapan CSR Sebagai Variabel Pemoderasi - Putra, Tebuana Agung; Muliartha RM, Ketut (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p29, 2019)
This study focussed to obtain empirical evidence of the effect of company growth on corporate value by disclosure of Corporate Social Responsibility (CSR) in manufacturing companies especially in the consumer goods sector that listed on the Indonesia Stock Exchange (IDX). This research was conducted at the consumer goods manufacturing company listed on the IDX. The sample is determined through non probability sampling method with purposive sampling technique. The number of observations obtained in this study is 60 data during the 2015-2017 observation period. The data analysis technique used is Moderated Regression Analysis (MRA). The results of this study indicate that company growth and CSR disclosure have no effect on firm value. Whereas the disclosure of CSR is able to moderate (strengthen) the influence of company growth on the value of the company. Keywords : Firm value, company growth, CSR disclosure